Interaction between posture and maxillomandibular deformity: a systematic review. Issue 1 (January 2022) - Kerbrat, A.; Schouman, T.; Decressain, D.; Rouch, P.; Attali, V.
Abstract: Maxillomandibular deformity (MMD) and body posture appear to be correlated. However, no systematic literature review of the available evidence to support this correlation has been performed to date. The aim of this study was to conduct a systematic literature review on posture and MMD. This systematic literature review was registered in the PROSPERO database. Systematic searches of the MEDLINE, Scopus, Cochrane Library, and Web of Science databases were performed. In total, 13 clinical studies were included. Nine found a significant association between MMD and body posture or body balance: two studies showed a correlation between increased cervical lordosis and skeletal class III MMD, two studies showed an interaction between mandibular deviation and scoliosis, four studies demonstrated a significant association between lumbar column and pelvis anatomy and MMD, and one study found a correlation between displacement of the centre of mass and MMD. However, the level of evidence is low; the methods used to evaluate body posture and MMD were inconsistent. Orthognathic surgery could modify body posture. Although there seems to be an interaction between body posture and facial deformity, the number of studies is too small and the level of evidence too low to strongly support this association.